A novel ground thermal recovery system for horizontal ground heat exchangers in a hot climate. (15th November 2020) - Sedaghat, Ali; Habibi, Mohammad; Hakkaki-Fard, Ali
Graphical abstract: Highlights: A novel ground thermal recovery system is proposed for horizontal GHEs. A three-dimensional quasi-steady CFD model of the system is developed. The performance of the proposed system is evaluated. The effect of various GHE geometric parameters on the COP of GSHP is investigated. The proposed recovery system can increase the COP of the system by up to 20.2%. Abstract: Ground Source Heat Pumps (GSHP), as a renewable source heating, ventilating, and air conditioning (HVAC) technology, has the highest energy efficiency among different heat pump types. One of the major drawbacks of GSHPs is the long-term ground temperature variations as a result of heat accumulation or depletion in the ground. This contribution puts forward a novel ground thermal recovery system for horizontal ground heat exchangers in a hot climate. The proposed recovery system consists of open-loop horizontal Ground-Air Heat Exchangers (GAHEs) that are buried between the horizontal Ground-Water Heat Exchangers (GWHEs). A fan supplies ambient air to the GAHE pipes when the soil around GWHE pipes is warmer than the ambient air, to remove the accumulated heat from the ground. A three-dimensional quasi-steady Computational Fluid Dynamics (CFD) model of the system is developed. This model is then used to evaluate the five years performance of the GSHP system with the proposed thermal recovery system for space cooling of a residential house in a hot desert climate. Moreover, the effect of various geometrical parameters, i.e., GWHE length, GWHE pipe spacing, GWHE buried depth, and GAHE pipe diameter on the system performance, are investigated. It is demonstrated that, by deploying the proposed recovery system, the five-year average annual Coefficient of Performance (COP) of the system can be increased by up to 20.2%. Moreover, applying the proposed recovery system not only enhances the ground thermal recovery but also improves the maximum cooling load that can be supplied to the building per unit land area. Furthermore, it is demonstrated that by applying the proposed recovery system, the average annual COP of the system gradually increases; however, it decreases for the GSHP without a recovery system.